Parallel Geometric Hashing Algorithm For Protein Tertiary Structure. - Jaber, Khalid; Abdullah, Rosni; Othman, Fazilah (Dr. Sang H. Lee, 2007)
The amount of protein structure has become very huge nowadays, which has led to the need for improving algorithms to cope with this exponential increase. At the same time, processors have become more powerful and affordable with low price.